Membrane Inovation for Proton Exchange Membrane Fuel Cells (PEMFCs) Based on Duck Feather Keratin Extract as Environmentally Friendly and Efficient Alternative Energy - Asih, Retno; Muhammad, Muhammad; Rahmadani, Oktab Bahar; Tiyarno, Melyana Putri; Lestari, Diah Suci; Sasmitaningrum, Indah Dwi (Proceeding of International Joint Conference on UNESA, 2024)
The interest in renewable and sustainable energy is increasing because it offers a clean and environmentally friendly approach. One system that produces renewable energy is a fuel cell, which produces electricity through electrochemical reactions. In fuel cells, the membrane has an important role in delivering the protons produced from the anode to the cathode. The membrane used can be replaced with an alternative membrane. Recent research into alternative 'green' membranes has become an exciting area of study. In this research, a proton-conducting keratin-based membrane was made from duck feather waste. Duck feather keratin extraction is carried out by dissolving the feathers in an alkaline solution and precipitating the supernatant obtained at the triple point. The phases contained in duck feathers and dry keratin that have been prepared, have been researched and are known to be related to the amide functional group which has an α-helical and β-sheet structure. Dry keratin exhibits agglomerated flat particles with a size of several microns. This indicates the potential of keratin derived from duck feathers for applications in fuel cell membranes.